Kepribadian Guru Dari Perspektif Siswa - Pasa, Janantri; Mahatma, Mahatma (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The purpose of this study was to identify the teacher's personality competencies according to the students' perspective. This research was conducted in June-July 2021. The method used in this study was a descriptive method in the form of a survey. The survey was conducted through a google form in the form of a questionnaire (questionnaire). The research instrument consisted of five indicators and 15 questions. The results show that students most like teachers who have personalities who present themselves as steady, stable, mature, wise and authoritative. Overall, according to the student's perspective, the teacher's personality competence is good and can be an example and role model for students.